Multicentre propensity score‐matched analysis of conventional versus extended abdominoperineal excision for low rectal cancer. Issue 7 (June 2014) - Ortiz, H.; Ciga, M. A.; Armendariz, P.; Kreisler, E.; Codina‐Cazador, A.; Gomez‐Barbadillo, J.; Garcia‐Granero, E.; Roig, J. V.; Biondo, S.; on behalf of the Spanish Rectal Cancer Project; Lujan, J.; Fraccalvieri, D.; et al.
<x xml:space="preserve">Abstract</x> Background Abdominal perineal excision (APE) was originally described with levator ani removal for rectal cancer. An even wider, more aggressive extralevator resection for APE has been proposed. Although some surgeons are performing a very wide 'extralevator APE (ELAPE)', there are few data to recommend it routinely. This multicentre study aimed to compare outcomes of APE and ELAPE. Methods A multicentre propensity case‐matched analysis comparing two surgical approaches (APE and ELAPE) was performed. All patients who underwent abdominoperineal resection of a rectal tumour were considered for the analysis. Tumour height was defined by magnetic resonance imaging measurement and patients with stage II–III tumours had neoadjuvant radiochemotherapy. Involvement of the circumferential resection margin (CRM) and intraoperative tumour perforation were the main outcome measures. A logistic regression model was used to study the relationship between the surgical approaches and outcomes. Results From January 2008 to March 2013 a total of 1909 consecutive patients underwent APE or ELAPE, of whom 914 matched patients (457 in each group) formed the cohort for analysis. Intraoperative tumour perforation occurred in 7·9 and 7·7 per cent of patients during APE and ELAPE respectively (P = 0·902), and there was CRM involvement in 13·1 and 13·6 per cent (P = 0·846). There were no differences between APE and ELAPE in terms of postoperative complication rates (52·3 versus 48·1 per cent; P = 0·209), need for reoperation (7·7 versus 7·0 per cent; P = 0·703), perineal wound problems (26·0 versus 21·9 per cent; P = 0·141), mortality rate (2·0 versus 2·0 per cent; P = 1·000) and local recurrence rate at 2 years (2·7 versus 5·6 per cent; P = 0·664). Conclusion ELAPE does not improve rates of CRM involvement, intraoperative tumour perforation, local recurrence or mortality.